Dependency of particle size distribution at dust emission on friction velocity and atmospheric boundary-layer stability - Y. Shao; J. Zhang; M. Ishizuka; M. Mikami; J. Leys; J. Leys; N. Huang (Atmospheric Chemistry and Physics, 2020)
Particle size distribution of dust at emission (dust PSD) is an essential quantity to estimate in dust studies. It has been recognized in earlier research that dust PSD is dependent on soil properties (e.g. whether soil is sand or clay) and friction velocity, u∗, which is a surrogate for surface shear stress and a descriptor for saltation-bombardment intensity. This recognition has been challenged in some recent papers, causing a debate on whether dust PSD is “invariant” and the search for its justification. In this paper, we analyse the dust PSD measured in the Japan Australian Dust Experiment and show that dust PSD is dependent on u∗ and on atmospheric boundary-layer (ABL) stability. By simple theoretical and numerical analysis, we explain the two reasons for the latter dependency, which are both related to enhanced saltation bombardment in convective turbulent flows. First, u∗ is stochastic and its probability distribution profoundly influences the magnitude of the mean saltation flux due to the non-linear relationship between saltation flux and u∗. Second, in unstable conditions, turbulence is usually stronger, which leads to higher saltation-bombardment intensity. This study confirms that dust PSD depends on u∗ and, more precisely, on the probability distribution of u∗, which in turn is dependent on ABL stability; consequently, dust PSD is also dependent on ABL. We also show that the dependency of dust PSD on u∗ and ABL stability is made complicated by soil surface conditions. In general, our analysis reinforces the basic conceptual understanding that dust PSD depends on saltation bombardment and inter-particle cohesion.